Grouping abstraction and authority control in policy-based spectrum management - ARGYROUDIS, PATROKLOS; FEENEY, KEVIN; LEWIS, DAVID; NOLAN, KEITH EDWARD; O'SULLIVAN, DECLAN (IEEE, 2007)
The management of dynamic spectrum access requires the coordination of administrative functions across multiple organizations, from regulators to secondary market operators and commons cooperatives. Policy-based management approaches to dynamic spectrum access must therefore support a wide range of organizational types and handle the relationships between policies authored separately within those organizations. A policy language for administering dynamic access to spectrum resources has been proposed by the DARPA XG initiative. This defines an expressive and extensible language for specifying policies that determine the correct behavior of RF transceivers as spectrum usage opportunities occur. However, this language does not yet address the mapping of policies onto the complex organizational settings that are likely to emerge in the dynamic spectrum access domain. This paper defines how the DARPA XG policy language can be integrated with a meta-policy management scheme that provides the powerful organizational modeling and policy authoring authority control needed to manage the evolution of policies in these complex organizational settings. The benefits of this integration are illustrated through a case study based on the potential use of dynamic spectrum access licenses granted in Ireland for the DySpan 2007 conference, and the organizational conflicts that even this simple scenario can yield. The practical issues of administering a multi-organizational policy management system are examined through an analysis of the interactions between existing components that are being assembled to demonstrate sophisticated policy management of a cognitive radio system.
PUBLISHED
Keywords: DARPA XG initiative RF transceivers administering dynamic access authority control cognitive radio system dynamic spectrum access management grouping abstraction meta-policy management scheme organizational modeling policy language policy-based spectrum management secondary market operators spectrum resources